THE ROLE OF ORAL HISTORY SOURCES IN INTERPRETING HISTORICAL EVENTS - Tugalova Madina Erkin qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Oral history has become a vital tool in modern historiography, particularly for studying marginalized communities and uncovering perspectives absent from written records. This article explores the methodological value, challenges, and impact of oral sources in interpreting historical events, with specific attention to the context of Central Asian history. By analyzing oral testimonies in parallel with traditional archival data, the paper argues for a more inclusive and dynamic reconstruction of the past.